Characteristics of a Bacteriophage, vB_Kox_ZX8, Isolated From Clinical Klebsiella oxytoca and Its Therapeutic Effect on Mice Bacteremia - Li, Ping; Zhang, Yangheng; Yan, Fuhua; Zhou, Xin (Frontiers in Microbiology, 2021)
Klebsiella oxytoca is an important nosocomial and community-acquired opportunistic pathogenic Klebsiella and has become the second most prevalent strain in the clinic after K. pneumoniae. However, there have been few reports of bacteriophages used for treating K. oxytoca. In this study, a novel bacteriophage, vB_Kox_ZX8, which specifically infects K. oxytoca AD3, was isolated for the first time from human fecal samples. The biological characteristics of vB_Kox_ZX8 showed an incubation period of 10 min, a burst size of 74 PFU/cell, and a stable pH range of 3–11. Genomic bioinformatics studies of vB_Kox_ZX8 showed that it belongs to the genus Przondovirus, subfamily Studiervirinae, family Autographiviridae. The genome of vB_Kox_ZX8 is 39,398 bp in length and contains 46 putative open reading frames encoding functional proteins, such as DNA degradation, packaging, structural, lysin-holin, and hypothetical proteins. We further investigated the efficacy of vB_Kox_ZX8 phage in the treatment of mice with bacteremia caused by Klebsiella oxytoca infection. The results showed that vB_Kox_ZX8 (5 × 109 PFU/mouse) injected intraperitoneally alone was metabolized rapidly in BALB/c mice, and no significant side effects were observed in the control and treatment groups. Importantly, intraperitoneal injection with a single dose of phage vB_Kox_ZX8 (5 × 107 PFU/mouse) for 1 h post-infection saved 100% of BALB/c mice from bacteremia induced by intraperitoneal challenge with a minimum lethal dose of K. oxytoca AD3. However, all negative control mice injected with PBS alone died. Owing to its good safety, narrow host infectivity, high lysis efficiency in vitro, and good in vivo therapeutic effect, phage vB_Kox_ZX8 has the potential to be an excellent antibacterial agent for clinical K. oxytoca-caused infections.